Rancang Bangun Aplikasi Pembukuan Keuangan UMKM Berbasis Website (Studi Kasus : UMKM Indah Fashion) - Ningtyas, Dita; Rivai, Irham (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Indah Fashion is one of the micro, small and medium enterprises (MSMEs) who engaged in clothing manufacturing services. The financial bookkeeping at Indah Fashion is still done manually by writing financial records in a ledger. This has caused problems such as recording errors in both income and expenses, incorrect transaction dates, miscalculations of raw material costs, and difficulties in creating financial reports. Based on the background of the above problems, it is necessary to create a bookkeeping application to assist MSMEs, especially Indah Fashion, in facilitating the creation of financial reports. The system development method used in this research is the waterfall method, which consists of the planning stage, problem analysis stage, system design stage including navigation structure design, system design using UML (Unified Modeling Language), application development stage, and system testing stage using blackbox testing method. Based on the results of the testing conducted on this system, it can be concluded that the website-based financial bookkeeping application for MSMEs has been successfully implemented according to the design and is free from syntax errors. Keywords: SMEs, Finance, Bookkeeping, Application, Website